Think-pair-square learning: Improving student’s collaborative skills and cognitive learning outcome on animal diversity course - Mustafa Ainul Yaqin; Sri Endah Indriwati; Herawati Susilo (University of Muhammadiyah Malang, 2018)
Empowering collaborative skills and optimizing learning outcomes are essential goals in every course. The aim of this study was to determine the effect of Think-Pair-Square (TPS) learning model on student collaborative skills and their cognitive learning outcomes. This study was Lesson-Study-based Classroom Action Research (CAR) carried out in two cycles. The subjects of this study consisted of 32 students who took Animal Diversity course. The CAR consisted of four phases i.e. planning, action, observation, and reflection. At the action phase, Lesson Study (LS) was conducted and consist of Plan, Do, and See. The instruments used were LS observation sheet, collaborative observation sheet, and cognitive test. The observation and test results of the both cycles were calculated and compared each other. There were improvements in the both student’s collaborative skills and cognitive learning outcome as high as 14% and 7.56, respectively. Therefore, TPS model can strengthen the student’s collaborative skills and cognitive learning outcome.